The influence of diet on gastrointestinal Candida spp. colonization and the susceptibility of Candida spp. to antifungal drugs - Małgorzata Jeziorek; Magdalena Frej-Mądrzak; Irena Choroszy-Król (Roczniki Panstwowego Zakladu Higieny, 2019)
Background. Candida spp. has been identified as the most common member of human gut microbiota. This yeast-like fungus is recognized as an opportunistic organism due to its potential to cause diseases in all parts of the gastrointestinal tract. Objective. The aim of the study was to investigate the relationship between diet and health of the study participants and the presence of gastrointestinal Candida spp. Susceptibility of Candida to antifungal drugs was determined. Material and methods. Material comprised of oral swabs and fecal samples self-collected by the study participants. The participants filled in a nutritional questionnaire. A total of 30 people took part in the study, including 28 women and 2 men. The study was conducted in Wroclaw, Poland. Susceptibility of Candida to antifungal drugs was determined using Bio-Rad’s FUNGITEST™ Kit designed for the susceptibility testing of yeasts to six antifungal drugs. Results. In the group with negative Candida spp. cultures, healthier wheat flour substitutes were consumed significantly more frequently than in the group with positive Candida spp. cultures. Yellow cheeses and quark were eaten significantly more frequently in the group with negative Candida spp. cultures. No antifungal resistance was detected in the study group. Conclusions. The increased consumption of purified wheat flour products was linked to the presence of gastrointestinal Candida spp. A higher consumption of cheese was observed in the group with negative Candida spp. cultures, which may indicate the inhibitory effect of saturated fatty acids on the growth of human Candida spp. Sensitivity of C. albicans to antifungal drugs may increase effectiveness of candidiasis treatment.